Intergenerational and early life influences on the well-being of Australian Aboriginal and Torres Strait Islander children: overview and selected findings from Footprints in Time, the Longitudinal Study of Indigenous Children. (2nd May 2018) - Salmon, M.; Skelton, F.; Thurber, K. A.; Bennetts Kneebone, L.; Gosling, J.; Lovett, R.; Walter, M.
Abstract: Footprints in Time : The Longitudinal Study of Indigenous Children (LSIC) is a national study of 1759 Australian Aboriginal and Torres Strait Islander children living across urban, regional and remote areas of Australia. The study is in its 11th wave of annual data collection, having collected extensive data on topics including birth and early life influences, parental health and well-being, identity, cultural engagement, language use, housing, racism, school engagement and academic achievement, and social and emotional well-being. The current paper reviews a selection of major findings from Footprints in Time relating to the developmental origins of health and disease for Australian Aboriginal and Torres Strait Islander peoples. Opportunities for new researchers to conduct further research utilizing the LSIC data set are also presented.